Pathophysiology of urinary incontinence in murine models. (6th November 2012) - Koike, Yusuke; Furuta, Akira; Suzuki, Yasuyuki; Honda, Mariko; Naruoka, Takehito; Asano, Koji; Egawa, Shin; Yoshimura, Naoki
Abstract Urethral closure mechanisms under stress conditions consist of passive urethral closure involving connective tissues, fascia and/or ligaments in the pelvis and active urethral closure mediated by hypogastric, pelvic and pudendal nerves. Furthermore, we have previously reported that the active urethral closure mechanism might be divided into two categories: (i) the central nervous control passing onto Onuf's nucleus under sneezing or coughing; and (ii) the bladder‐to‐urethral spinal reflex under Valsalva‐like stress conditions, such as laughing, exercise or lifting heavy objects. There are over 200 million people worldwide with urinary incontinence, a condition that is associated with a significant social impact and reduced quality of life. Therefore, basic research for urinary continence mechanisms in response to different stress conditions can play an essential role in developing treatments for stress urinary incontinence. It has been clinically shown that the etiology of stress urinary incontinence is divided into urethral hypermobility and intrinsic sphincter deficiency, which could respectively correspond to passive and active urethral closure dysfunction. In this review, we summarize the representative stress urinary incontinence animal models and the methods to measure leak point pressures under stress conditions, and then highlight stress‐induced urinary continence mechanisms mediated by active urethral closure mechanisms, as well as future pharmacological treatments of stress urinary incontinence. In addition, we introduce our previous reports including sex differences in urethral closure mechanisms under stress conditions and urethral compensatory mechanisms to maintain urinary continence after pudendal nerve injury in female rats.